Testing strategies and failure modes of dimpled laminate plates. (July 2019) - Affolter, Ch.; Barbezat, M.; Piskoty, G.; Steger, R.; Terrasi, G.
Abstract: Ground reinforcing plates are designed to facilitate the access of rescue vehicles and equipment in soft and muddy ground, e.g. for fire engines and cranes. Such plates have to be light and easy to handle, hence the use of composite materials is favourable. The investigated 'dimpled plates' are designed with glass fibre reinforced polymer (GFRP) and built to withstand high loads and to allow maximum deformation. Design parameters for the dimensioning of the plates are derived from standard ASTM laminate testing, and the values are used for the optimization of the plates by means of FEM (shape; composites layup). The verification of the component resistance and strength, however, requires adapted test configurations and procedures. Global loading of the structure has to replicate the situation in the field, and the resulting failure modes have to be identified for further optimization of the system. The scale of the plate bending tests had to be minimized due to large deflections. Mainly shear failure (delamination) and compressive failure (fibre buckling or crushing) were observed. Negative boundary effects had to be minimize in the tensile test, too. Fibre tensile failure followed after delaminations in the fillet of the knop base. Transverse compression: Testing against hard parallel plates provided high strength values, but the setup did not reproduce the situation of a soft bedding in the field, with mud. Different scenarios of elastic bedding over rubber plates were compared. The results provided the basis to optimize the material choice for the laminate (resin type, fibre reinforcement). The durability of the final composite laminates was verified with extensive aging tests in a later study. Highlights: Dimpled laminate plates with long fibre reinforcement were optimized. The triaxial GFRP laminate accounts for producibility and performance. Mechanical testing of the parts was compared to standard laminate characterization. Size and boundary effects dictate minimum sample sizes and test setups. Plate tensile and bending strength are 50–100% of the plane laminate strength.